(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Nanotechnology emerged as gift to mankind, with great potential in a broad variety of areas of research and our everyday life. In contrast to conventional biosensors, the application of nanotechnology in the creation of biosensors results in a highly effective nano-biosensor with a tiny shape. Nano- and Nano sensors based keen delivery systems can be used to monitor the release of agrochemicals for pest and pathogen defense, to detect the presence of plant viruses, to determine soil nutrient content, and to release nano-encapsulated slow-release fertilizers without wasting them by leaching. As a consequence, there is a lot of optimism that such robots may assist maintain agriculture by boosting output and productivity. Nanotechnology has emerged as a gift to mankind, with great potential in a broad variety of areas of research and in our everyday lives. As nanotechnology is utilized to improve biosensors, it results in a more resilient nano-biosensor with a smaller structure than conventional biosensors. Nano biosensors may detect wide variety of fertilizers, herbicides, pesticides, insecticides, bacteria, moisture, and soil pH, among other things. When utilized correctly and in a controlled way, nano-biosensors may assist to promote sustainable agriculture and impro